Penerapan Water Tepid Sponge Terhadap Demam pada Anak Usia Toddler - Arista, Vivin; Husain, Fida' (Barongko: Jurnal Ilmu Kesehatan, 2023)
Background: If body temperature exceeds the normal range of 36.5-37.5°C, it can be said to have a fever. Water tepid sponge is applying warm water compresses with a temperature of 37°C for 15 minutes on several places that have large blood vessels such as on the neck, armpits, groin, plus wiping the back and chest. Objective: to determine the difference in body temperature before and after applying the water tepid sponge. Method: Treating fever with water tepid sponge therapy using a descriptive research method with a case study approach. The focus of this case study is the application of a water tepid sponge to toddler patients (1-3 years) with fever by comparing 2 similar case studies. Results: Fever treatment with water tepid sponge given 2 times a day with a duration of 15 minutes in 1 meeting. From the two respondents, it was found that An. D experienced a decrease in body temperature from 38.7°C to 36.8°C. Meanwhile An. R, before therapy was given, the body temperature was 39.0°C to 36.7. There is a decrease in body temperature after doing the water tepid sponge. Conclusion: Water tepid sponge therapy can reduce fever in toddler-aged children who have fever